Human Resources Development Collaboration Between Boarding School Management and Technology - Khusna, Atina Novia; Fahmi, Nurkafidz Nizam; Fiqhiyah, Kuni Usisatil (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
This study analyzes the strategy for developing santri resources through collaboration between boarding school management and technology at one of the Islamic educational institutions in Indonesia. As an Islamic educational institution, boarding school face challenges in preparing santri with both strong religious understanding and competencies relevant to the digital era. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation, informants in this interview were purposive, namely individuals who have insights and experiences relevant to the focus of the research. The number of informants interviewed was 25 people, consisting of the head of the foundation, principal, teachers, and students. The selection of these informants aims to obtain in-depth and comprehensive data on the development of human resources in collaboration between Islamic boarding school management and technology, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The research findings show that the strategy for developing Islamic boarding school resources involves integrating technology into learning, providing digital-based skills training, and collaborating with various stakeholders to increase access to modern educational resources. Islamic boarding school management plays an important role in formulating adaptive policies, while technology applications include digitalization of teaching materials, online-based learning, and the use of educational applications. The main challenges in its implementation include limited infrastructure, human resource readiness, and resistance to change. However, effective collaboration between Islamic boarding school management, educators, and external stakeholders improves the quality of Islamic boarding school students in terms of academics, skills, and readiness for the modern world. This study highlights that collaboration between Islamic boarding school management and technology is a strategic step in developing Islamic boarding school resources in the digital era.